Evaluation of the Expression Levels of Immunohistochemical Markers BCL-2, And KI-67 in Secondary Placental Insufficiency (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In secondary placental insufficiency, inflammatory processes are often morphologically detected in placental tissue, each manifesting with specific changes. Placental insufficiency is a syndrome based on morphofunctional changes in the placenta, which, when progressing, leads to delayed fetal growth and the development of hypoxia. Therefore, improving the diagnosis of various forms of placental insufficiency during pregnancy is one of the important issues in modern morphology. Immunohistochemical (IHC) analysis is a crucial diagnostic and research method in modern medicine and biology.Studies aimed at assessing the expression levels of immunohistochemical markers such as Ki-67 and Bcl-2 as well as the comparative analysis of morphometric indicators of tissue structures in histological forms of placental tissue in secondary placental insufficiency, hold significant scientific and practical importance.